ANALISIS PENGARUH PENAMBAHAN LIMBAH STYROFOAM PADA ASPAL POROS AC WC TERHADAP DURABILITAS DAN FLEKSIBILITASNR - Rosyad, Farlin; Sari, Intan Permata (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The availability of roads is an absolute requirement for the entry of investment into an area, for this reason it is necessary to plan for pavement that is strong, durable and has high resistance to plastic deformation. Damage in Indonesia is generally caused by excessive loading. This cause of damage to road pavement requires the use of higher quality materials for road pavement in the form of aggregate material as a filler or asphalt as a binder. The addition of Styrofoam waste to the asphalt concrete mixture is a solution for road planning and reducing Styrofoam waste pollution resulting from household waste. From the results of the addition of the Styrofoam waste mixture affecting the survivability and flexibility of the asphalt, the Marshall quotient and residual Marshall Stability values which affect the durability and flexibility when compared to the normal mixture decreased, the decrease in value was due to the large number of cavities in the test object mixed with Styrofoam waste. From the results of the Styrofoam waste mixture, the Marshall Stability optimization value for the 10% Styrofoam waste percentage was 91,45 kg/mm and for the Marshall Quotient the 10% Styrofoam waste percentage was 356 kg/mm